D-Dimer Predicts Long-Term Cause-Specific Mortality, Cardiovascular Events, and Cancer in Patients With Stable Coronary Heart Disease: LIPID Study. Issue 7 (14th August 2018) - Simes, John; Robledo, Kristy P.; White, Harvey D.; Espinoza, David; Stewart, Ralph A.; Sullivan, David R.; Zeller, Tanja; Hague, Wendy; Nestel, Paul J.; Glasziou, Paul P.; Keech, Anthony C.; Elliott, John; et al.
Abstract : Background: D-dimer, a degradation product of cross-linked fibrin, is a marker for hypercoagulability and thrombotic events. Moderately elevated levels of D-dimer are associated with the risk of venous and arterial events in patients with vascular disease. We assessed the role of D-dimer levels in predicting long-term vascular outcomes, cause-specific mortality, and new cancers in the LIPID trial (Long-Term Intervention with Pravastatin in Ischaemic Disease) in the context of other risk factors. Methods: LIPID randomized patients to placebo or pravastatin 40 mg/d 5 to 38 months after myocardial infarction or unstable angina. D-dimer levels were measured at baseline and at 1 year. Median follow-up was 6.0 years during the trial and 16 years in total. Results: Baseline D-dimer levels for 7863 patients were grouped by quartile (⩽112, 112–173, 173–273, >273 ng/mL). Higher levels were associated with older age, female sex, history of hypertension, poor renal function, and elevated levels of B-natriuretic peptide, high-sensitivity C-reactive protein, and sensitive troponin I (each P <0.001). During the first 6 years, after adjustment for up to 30 additional risk factors, higher D-dimer was associated with a significantly increased risk of a major coronary event (quartile 4 versus 1: hazard ratio [HR], 1.45; 95% confidence interval, 1.21–1.74), major cardiovascular disease (CVD) event (HR, 1.45; 95% confidence interval, 1.23–1.71) and venous thromboembolism (HR, 4.03; 95% confidence interval, 2.31–7.03; each P <0.001). During the 16 years overall, higher D-dimer was an independent predictor of all-cause mortality (HR, 1.59), CVD mortality (HR, 1.61), cancer mortality (HR, 1.54), and non-CVD noncancer mortality (HR, 1.57; each P <0.001), remaining significant for deaths resulting from each cause occurring beyond 10 years of follow-up (each P ⩽0.01). Higher D-dimer also independently predicted an increase in cancer incidence (HR, 1.16; P =0.02).The D-dimer level increased the net reclassification index for all-cause mortality by 4.0 and venous thromboembolism by 13.6. Conclusions: D-dimer levels predict long-term risk of arterial and venous events, CVD mortality, and non-CVD noncancer mortality independent of other risk factors. D-dimer is also a significant predictor of cancer incidence and mortality. These results support an association of D-dimer with fatal events across multiple diseases and demonstrate that this link extends beyond 10 years' follow-up. Abstract : Supplemental Digital Content is available in the text.